Low prostaglandin E2 and cyclooxygenase expression in nasal mucosa fibroblasts of aspirin‐intolerant asthmatics. Issue 4 (25th April 2013) - Roca‐Ferrer, Jordi; Pérez‐Gonzalez, Maria; Garcia‐Garcia, Francesc J.; Pereda, Javier; Pujols, Laura; Alobid, Isam; Mullol, Joaquim; Picado, Cesar
Abstract Background and objective Anomalies in the regulation of cyclooxygenase (COX)‐1 and ‐2 have been described in nasal polyps of aspirin‐induced asthma (AIA). Whether these anomalies are specific to nasal polyps or affect all the nasal mucosa (NM) of upper airways is still unclear. The objective of this study was to compare the COX pathway in NM of AIA patients with the NM of control subjects. Methods Fibroblasts were isolated from NM of five AIA patients (AIA‐NM) and five control subjects (control‐NM). Cells were treated with 10 ng/mL interleukin (IL)‐1β for up to 72 h. Prostaglandin E2 (PGE2) production was measured by enzyme‐linked immunosorbent assay (ELISA), expression of COX‐1 protein by Western blot and COX‐2 protein by ELISA, Western blot and immunofluorescence techniques. Results IL‐1β increased PGE2 production and COX‐1 protein expression in control‐NM fibroblasts, but no changes were found in AIA‐NM. IL‐1β provoked a significant time‐dependent increase in COX‐2 protein expression in control‐NM fibroblasts but had a very mild effect on COX‐2 protein expression in AIA‐NM. Conclusions Our data suggest that abnormalities in the COX pathway are not a phenomenon exclusive to nasal‐polyp mucosa as they are also present in all the NM of AIA patients. These anomalies may be involved in the pathogenesis of airway inflammation and non‐steroidal anti‐inflammatory drug intolerance in asthma patients with chronic rhinosinusitis and nasal polyposis.